2001
DOI: 10.1007/bf03020379
|View full text |Cite
|
Sign up to set email alerts
|

The laryngeal mask airway is effectièe (and probably safe) in selected healthy parturients for electièe Cesarean section: a prospectièe study of 1067 cases

Abstract: Purpose: To report on the use of the laryngeal mask airway (LMA) for elective Cesarean section in 1067 consecutive ASA I-II patients preferring general anesthesia.Methods: Patients were excluded if they had pharyngeal reflux, a pre-pregnancy body mass index >30, or had a known/predicted difficult airway. Patients were fasted for six hours and given ranitidine/sodium citrate. A rapid sequence induction was performed with thiopentone and suxamethonium. The LMA was inserted by experienced users. Anesthesia was ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
67
1
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(105 citation statements)
references
References 25 publications
(19 reference statements)
7
67
1
5
Order By: Relevance
“…27 Despite the low incidence of aspiration (1:667), even in the high-risk population, 28 there is still a need for prospective studies powered adequately to validate the safety of supraglottic devices in protecting against aspiration during anesthesia. Han et al 29 found no cases of aspiration in 1,060 patients who underwent elective LSCS with a LMA Classic TM , and Halaseh et al 30 found no cases of aspiration in 3,000 patients who underwent elective LSCS with a PLMA. Our data will add to the current available literature on the use of supraglottic airway devices and the risk of aspiration in parturients.…”
Section: Slma and Risk Of Aspirationmentioning
confidence: 99%
“…27 Despite the low incidence of aspiration (1:667), even in the high-risk population, 28 there is still a need for prospective studies powered adequately to validate the safety of supraglottic devices in protecting against aspiration during anesthesia. Han et al 29 found no cases of aspiration in 1,060 patients who underwent elective LSCS with a LMA Classic TM , and Halaseh et al 30 found no cases of aspiration in 3,000 patients who underwent elective LSCS with a PLMA. Our data will add to the current available literature on the use of supraglottic airway devices and the risk of aspiration in parturients.…”
Section: Slma and Risk Of Aspirationmentioning
confidence: 99%
“…24 Yao's study is therefore underpowered for its primary end point. However, with the previous two series, 5,6 we now have data on 4,643 low-risk women undergoing elective CD with an LMA with no documented cases of aspiration and one case of regurgitation. It is very important to point out though that the estimate of aspiration of 1:1000 likely includes patients at higher risk for aspiration, not the carefully selected lowrisk women included in the studies of LMA in CD in whom the incidence of aspiration is probably much lower.…”
mentioning
confidence: 87%
“…3,4 In 2001, Han reported the use of the LMA Classic TM in 1,067 parturients undergoing elective CD. 5 More recently, Halaseh et al described their experience using the LMA ProSeal TM (PLMA) in 3,000 women undergoing the same procedure. 6 Both studies reported no cases of aspiration, but there was one case of regurgitation.…”
mentioning
confidence: 99%
See 2 more Smart Citations